Determining best practice in performance monitoring and evaluation of sport coaches: Lessons from the traditional business environment - O'Boyle, I. (International Journal of Sports Science and Coaching, 2014)
This article undertakes a review of traditional performance management appraisals against 360-degree feedback applied to the sport coaching setting. The role of the coach is central to the overall performance of any team or athlete and how this performance is managed and evaluated may have significant impacts on overall sporting success. The benefits and challenges of both traditional performance appraisals and 360-degree feedback are outlined within this review and it is argued that although at potentially greater time cost to an organisation, 360-degree feedback for coaches is a superior method of managing and evaluating coaching performance therefore potentially facilitating high levels of sustainable long-term sporting success.